2019
DOI: 10.1097/mol.0000000000000604
|View full text |Cite
|
Sign up to set email alerts
|

HDL from an Alzheimer's disease perspective

Abstract: Purpose of review We review current knowledge regarding HDL and Alzheimer's disease, focusing on HDL's vasoprotective functions and potential as a biomarker and therapeutic target for the vascular contributions of Alzheimer's disease. Recent findings Many epidemiological studies have observed that circulating HDL levels associate with decreased Alzheimer's disease risk. However, it is now understood that the functions of HDL may be more informative than le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 181 publications
1
79
0
1
Order By: Relevance
“…It has been established that keeping BP in the normal range is an effective strategy for the prevention of primary and secondary dementia. HDL has numerous beneficial functions including preventing amyloid beta aggregation [26] and protecting against amyloid beta-induced inflammation [27]. However, there has been no study to elucidate the correlation between blood pressure and the HDL-C level in the adult population aged 20-80 years.…”
Section: Discussionmentioning
confidence: 99%
“…It has been established that keeping BP in the normal range is an effective strategy for the prevention of primary and secondary dementia. HDL has numerous beneficial functions including preventing amyloid beta aggregation [26] and protecting against amyloid beta-induced inflammation [27]. However, there has been no study to elucidate the correlation between blood pressure and the HDL-C level in the adult population aged 20-80 years.…”
Section: Discussionmentioning
confidence: 99%
“…We identified a unique cell type-specific signal between microglia and genetic variants associated with High-density lipoprotein (HDL) cholesterol level (q MAGMA = 0.046) (Figure 2a). Given the role of lipids in AD 15,16 , we asked whether the HDL cholesterol association was related to the association between AD risk and microglia gene expression (Figure 2a). However, conditional analysis suggests distinct genetics underlie the associations of AD and HDL cholesterol levels with microglia ( Supplementary Figure 8).…”
Section: The Single-cell Profiles Of the Substantia Nigra Inform On Tmentioning
confidence: 99%
“…A recent meta-analysis reported no signi cant association between HDL-C and AD risk [23]. The protective effects of HDL-C on AD risk have been observed in middle-aged adults, while studies examining patients ≥70 years of age have reported no such association [28]. Furthermore, these observational studies had limited sample sizes of <10,000 [23].…”
Section: Discussionmentioning
confidence: 99%